If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14 + -1x + 3 = 6x + 17 + -3x Reorder the terms: 14 + 3 + -1x = 6x + 17 + -3x Combine like terms: 14 + 3 = 17 17 + -1x = 6x + 17 + -3x Reorder the terms: 17 + -1x = 17 + 6x + -3x Combine like terms: 6x + -3x = 3x 17 + -1x = 17 + 3x Add '-17' to each side of the equation. 17 + -17 + -1x = 17 + -17 + 3x Combine like terms: 17 + -17 = 0 0 + -1x = 17 + -17 + 3x -1x = 17 + -17 + 3x Combine like terms: 17 + -17 = 0 -1x = 0 + 3x -1x = 3x Solving -1x = 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -1x + -3x = 3x + -3x Combine like terms: -1x + -3x = -4x -4x = 3x + -3x Combine like terms: 3x + -3x = 0 -4x = 0 Divide each side by '-4'. x = 0 Simplifying x = 0
| (Y^5)-(Y^2)-3=0 | | (x*500)+((x-1)*500)=5000 | | (x*500)+((x-1)*500)=3000 | | 0=2y-6 | | 0.07(30)+0.5(60-30)= | | -8x-3=9x+4x+18 | | 3(2y+4)=36 | | 3x+2x+3y=90 | | 8(z-4)=32 | | -x+25= | | 7(2x+2)=28 | | Log^4(5x-3)=1 | | y=3y-2 | | y-325=2(x-75) | | 2(5x-10)=40 | | 0.05x+0.12(7000-x)= | | 3y+16=15-68 | | 4(3z-8)=-20 | | 3x-36+2x+36=180 | | 5(z-1)=20 | | 3x-36+2x+36=189 | | 50x+8-23x=15+10x-20 | | 7(y-7)=-14 | | 1200-0.07(7000)= | | -x^2+17x-60=0 | | (2+7x-5(3x-1))=7x-16-x | | 4-x=2(x-5)-19 | | 6(2z-7)=18 | | 9y+12=-20y-4 | | 2(5x-6)=-2 | | 0=4x^2+4x+1 | | 3(3y+2)=42 |